The association between adult ADHD and food addiction: A mediation analysis. (1st December 2021) - Samela, Tonia; Innamorati, Marco; Lester, David; Raimondi, Giulia; Giupponi, Giancarlo; Imperatori, Claudio; Contardi, Anna; Fabbricatore, Mariantonietta
Abstract: Objectives: The aim of this study was to investigate the association between food addiction severity (FA) and ADHD symptomatology. Furthermore, we investigated whether emotional distress, and the mentalization deficits could mediate this relationship. Methods: Three hundred eighty-five Italian adults (307 women and 78 men) participated in the study and completed the Italian versions of the Modified Yale Food Addiction Scale version 2.0, the Adult ADHD Self-Report Scale, the Depression Anxiety Stress Scales 21 and the Mentalization Questionnaire. Results: ADHD symptoms severity and general distress were significantly and independently associated with FA. Emotional distress partly mediated the relationship between FA and ADHD symptoms severity. In addition, mentalization deficits partly mediated this relationship only when evaluating the influence of FA on ADHD symptoms severity. Limitations: This is a cross-sectional study and causal interpretations of the relationships among the variables are speculative. Conclusions: It is important to assess emotional distress and mentalization deficits in individuals at risk of ADHD and FA because these conditions could increase the risk for the presence of disordered eating patterns.